The communication style of Wahhabi preaching and the teachings of the Prophet Muhammad - Ujang Mahadi; Wahyu Abdul Jafar (Pharos Journal of Theology, 2023)
This study aims to determine whether the communication style of preaching that Wahhabis have carried out follows the teachings of the Prophet Muhammad. So far, Wahhabis have always claimed that Wahhabism is the most sunnah teaching; even clerics from their group get the title of Sunnah priest, while Priests not in line with Wahhabism are labeled as heretics. This study is based on a descriptive literature research approach. The data collection technique used in this research was a literature study. At the same time, the analysis technique used in this research was descriptive. After conducting in-depth research, it was concluded that the preaching communication style that the Wahhabis have carried out is not essentially adhering to the teachings of the Prophet Muhammad. Several things cause this discrepancy. First, the Prophet's Preaching is Holistic, not focused on a particular theme. In preaching, the Prophet Muhammad did it in a very balanced way. The Prophet preached the issue of monotheism, fiqh, and morality in an integrated manner without highlighting one side or the other. Preaching the Prophet like this was not followed by the Wahhabis. The Wahhabis, in their preaching, only focus on the purification of monotheism. Second, Wahhabis misunderstand the meaning of bid'ah (heretical) hadith. Wahhabis categorically reject all local traditions that did not exist at the time of the Prophet, even though the Prophet Muhammad's hadith about heresy should be properly understood. The bid'ah prohibited in the hadith is dolalah bid'ah, while the hasanah bid'ah is not forbidden and is even highly recommended. Third, Wahhabis are seemingly commiting crimes by falsifying the books of the ahlu sunah wal jamah scholars. Wahhabis changed the contents of the Book, which was initially not following the teachings of Wahhabism, and they were altered to be in line with Wahhabism.